(3GdCSGdjH GdMOjKI ddJMdjd GdeGdj hEYOGO GdehGRfGJ dCZQGV GdJNWjW hGdQbGHIs ((3GdbGgQI(B:s (3GdTQcI GdYQHjI GdeJMOI ddJShjb hGdJhQjOGJ(B,s, 2008)
(3jVe GdJMdjd GdeGdj heJWdHGJg, CSGdjH GdJMdjd GdeGdj , eJWdHGJ GdJMdjd GdeGdj , JMdjd GdSjIdI aj GdefXeI , JMdjd GdQHMjI aj GdefXeI, JMdjd eUGOQ GdCehGd hGSJNOGegG aj GdefWbI, GdehGRfGJ dCZQGV GdJNWjW hGdQbGHI, hXGFa hCfhGY GdehGRfGJ, JNWjW GdQHM hGdehGRfGJ GdJNWjWjI, GdehGRfI GdJNWjWjI hOhQgG aj EJNGO GdbQGQGJs
(3GdeQGLY U(B.121s
Keywords: (3GdJNWjWs; (3GdJbGQjQ GdeGdjIs; (3GdQbGHIs; (3GdejRGfjIs